Mechanical Analysis of the Veterinary Cuttable Plate - Fruchter, A. M.; Holmberg, D. L. (Veterinary and Comparative Orthopaedics and Traumatology, 1991)
A laboratory model was chosen to compare the stiffness of various small bone plates during the application of a bending force. Forces were applied to and measured from the plate surface directly. Other compressible materials were not in contact with the supporting or measuring devices. Although we cannot recommend from this experimental model that the stiffest plate would be the best treatment option, we can conclude that: (1) the stiffness of two stacked veterinary cuttable plates was approximately equal to the sum of the stiffness for each plate, (2) screw size did not have an effect on the stiffness of the veterinary cuttable plate in three out of four comparisons, and (3) single and stacked veterinary cuttable plates were stiffer than mini bone plates accepting 1.5 mm and 2.0 mm cortical screws and less stiff than the 2.7 mm dynamic compression plate.
Keywords: Cuttable plate; stiffness